Matthew - Quarles, Charles L. 1965-; Köstenberger, Andreas J. 1957-; Yarbrough, Robert W. 1953- (Nashville B&H Publishing Group, 2017)
The Exegetical Guide to the Greek New Testament (EGGNT) closes the gap between the Greek text and the available lexical and grammatical tools, providing all the necessary information for greater understanding of the text..
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Kommentar